Analysis Of The Level Of Acceptance And Satisfaction Of QRIS Payment Technology Users Using TAM And EUCS - Nabila Azahra; Cecep Warman; Rieska Rahayu Ayuningsih (International Journal of Health Engineering and Technology, 2026)
The rapid development of digital payment technology has accelerated the adoption of the Indonesian Quick Response Code Standard (QRIS) as a practical and efficient payment method. Generation Z, particularly students, is one of the main user groups due to their high level of digital literacy and technology adoption. This study aims to analyze the acceptance of QRIS technology using the Technology Acceptance Model (TAM), evaluate user satisfaction through the End User Computing Satisfaction (EUCS) model, and examine the relationship between technology acceptance and user satisfaction among students at Nusa Putra University. A quantitative research approach was employed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS software. Data were collected through questionnaires distributed to 155 Generation Z students who had experience using QRIS. The findings indicate that both technology acceptance and user satisfaction are categorized as very high. Perceived Usefulness, Behavioral Intention, Accuracy, and Format significantly influence user satisfaction, whereas Perceived Ease of Use, Content, Ease of Use, and Timeliness show no significant effect. The model demonstrates moderate explanatory power of Behavioral Intention (R2=0,589) and strong explanatory power for User Satisfaction (R2=0,839). Furthermore, Behavioral Intention positively mediates the relationship between technology acceptance and user satisfaction.